Optimization of a 96-Well Electroporation Assay for Postnatal Rat CNS Neurons Suitable for Cost–Effective Medium-Throughput Screening of Genes that Promote Neurite Outgrowth - Hutson, Thomas; Buchser, William J.; Bixby, John L.; Lemmon, Vance P.; Moon, Lawrence D. (Frontiers in Molecular Neuroscience, 2011)
Following an injury, central nervous system (CNS) neurons show a very limited regenerative response which results in their failure to successfully form functional connections with their original target. This is due in part to the reduced intrinsic growth state of CNS neurons, which is characterised by their failure to express key regeneration-associated genes (RAGs) and by the presence of growth inhibitory molecules in CNS environment that form a molecular and physical barrier to regeneration. Here we have optimised a 96-well electroporation and neurite outgrowth assay for postnatal rat cerebellar granule neurons cultured upon an inhibitory cellular substrate expressing myelin-associated glycoprotein or a mixture of growth-inhibitory chondroitin sulphate proteoglycans. Optimal electroporation parameters resulted in 25% transfection efficiency and 50% viability for postnatal rat cerebellar granule neurons (CGNs). The neurite outgrowth of transduced neurons was quantitatively measured using a semi-automated image capture and analysis system. The neurite outgrowth was significantly reduced by the inhibitory substrates which we demonstrated could be partially reversed using a Rho Kinase inhibitor. We are now using this assay to screen large sets of RAGs for their ability to increase neurite outgrowth on a variety of growth inhibitory and permissive substrates.